Perancangan Dan Implementasi Konsep Bussines To Costumer (B2C) Di CV.Biak Divers Berbasis Web - Hendra Manginsela; Steven R. Sentinuwo; Virginia Tulenan (Jurnal Teknik Elektro dan Komputer, 2016)
Abstract-, The design and implementation of the concept of business to consumer (b2c) at Biak Divers WEB-based support work efficiency and effectiveness in processing the data to provide information needed by the customer. The purpose of writing this final project to study, analyze, design and implement web-based information system BiakDivers using PHP and Mysql. The software developed in the preparation of this final project using HTML (Hypertext Markup Language), which is the basis for web scripting language and is client sideyang allows displaying the information in text form, chart, and also to connect between each display Web Page (Hyperlink). It is also used PHP and MySQL to develop information systems to be accurate. The end result of this research is produced Web-based application program that can give a clear overview of the Information System and the implementation of business processes (B2C) as the promotional efforts and means to facilitate customer ordering dive packages and dive organizations that will be followed. Keywords: Bussinness To Consumer, Divers,Information,Website. Abstrak-, Perancangan dan implementasi konsep business to consumer (b2c) pada Biak Divers Berbasis WEB menunjang efisiensi dan efektifitas kerja dalam mengolah data untuk memberikan informasi yang dibutuhkan pelanggan. Tujuan penulisan Tugas Akhir ini untuk mempelajari, menganalisis, merancang dan mengimplementasikan sistem informasi berbasis web BiakDivers dengan menggunakan  PHP dan Mysql. Perangkat lunak yang dikembangkan dalam penyusunan Tugas Akhir ini menggunakan HTML(Hypertext Markup Language) yang merupakan bahasa dasar untuk web scripting dan bersifat clientsideyang memungkinkan menampilkan informasi dalam bentuk teks, grafiks, dan juga untuk menghubungkan antar tampilan WebPage (Hyperlink). Selain itu juga digunakan program PHP dan MySQL untuk membuat sistem informasi menjadi akurat. Hasil akhir dari penelitian ini adalah dihasilkan program aplikasi berbasis Web yang dapat memberikan gambaran jelas mengenai Sistem Informasi Dan implementasi proses bisnis (B2C) sebagai upaya promosi dan sarana untuk mempermudah pelanggan memesan paket penyelaman dan organisasi penyelaman yang akan diikuti. Kata Kunci :Bussinness To Consumer,  Divers, Information,Website.